Thu bột cơ học P-RC-APMP cho độ trắng cao từ gỗ keo tai tượng - Sơn, Cao Văn; Sành, Đào Sỹ; Hoà, Doãn Thái (Vietnam Journal of Chemistry, 2012)
A study of optimized impregnation of the hard wood species (Acacia mangium) in P-RC-APMP process, using different impregnation conditions was presented. The doses of sodium hydroxide and hydrogen peroxide were 2.1% and 5.0% (vs. oven dried wood), respectively, with impregnating time of 17.5 minutes gave good P-RC-APMP pulp with brightness of » 80% ISO, tensile breaking length of 4730 m, tear index of 4 mN.m2/g and burst index of 2 kPa.m2/g. The pulp may be used for productions of different printing paper grades.